THERMAL MOISTURE TRANSFER IN SOIL - Ismaylov Haliq Shadmanovich (Web of Journals Publishing, 2025)
One of the main mechanisms for supplying moisture to the upper layers of soil is its capillary-sorptive transfer, caused by moisture loss due to evaporation from the soil surface and transpiration by plants. Very complex alternatives arise for plant roots under conditions of deep plowing. They must: - either “catch up” with the moisture as the upper soil horizons dry out rapidly (as is observed in nature); - or wait for the moisture to rise upward. However, deep plowing hinders both of these processes, as it destroys the capillary properties of the plowed soil horizon, contributes to its rapid drying, and at the same time creates a plow pan beneath it. This impedes both root penetration into deeper layers and the upward movement of moisture.
Keywords: Thermo-moisture transfer, capillary-sorptive, creeping (moisture movement), depth gradients, condensation-related, plant roots.